The many faces of multilingualism language status, learning and use across contexts - Guardado Rodríguez, Martín; Romanowski, Piotr, 1973- (Trends in applied linguistics ;, 2020)
The series Trends in Applied Linguistics meets the challenges of the rapidly growing field of applied linguistics. In a very broad sense, applied linguistics is understoodby focusing on the application of theoretical linguistics to current problems arising in different contexts of human society. Given the interdisciplinary character of applied linguistics, the series includes cognitive, psycholinguistic, sociolinguistic and educational perspectives. The following topicsare included in the series: Second language acquisition and the acquisition of additional languages Bilingual and multilingual.